POLARIZED NEUTRON REFLECTION EXPERIMENT ON AN FE-AL2O3 ANTIGRANULOCYTES FILM - Felici, R; Fiorani, D; Dormann, J; Penfold, J; Ward, R (1990)
We present results of polarized neutron reflection measurements on an FeAl2O3 granular film. The results show a saturated static magnetization which corresponds to 55% of the bulk iron value. The magnetization curve has been interpreted using theories developed for granular superparamagnets. © 1990.